A study of modified Hermite polynomials of two variables - Ahmad Khan, Mumtaz (2013)
The present paper is a study of modied Hermite polynomials of two variables Hn(x; y; a) which for a = e reduces to Hermite polynomials of two variables Hn(x; y) due to M.A. Khan and G.S. Abukhammash.